Meningkatkan Wawasan Nusantara Menggunakan Bahasa Indonesia sebagai Bahasa Pengantar di SD Internasional Bekasi - Fransiska Wahyuningsih; Maria Melani Ika Susanti (Jurnal Studi Guru dan Pembelajaran, 2024)
The issue faced by students studying in international schools is their proficiency in the Indonesian language and their knowledge about Indonesia. This is due to the students predominantly using English as the medium of instruction both inside and outside the classroom. In light of this, the purpose of this research is to provide an overview of the Indonesian language proficiency and national insight of 5th grade students in an International Baccalaureate (IB) curriculum-based international school. The method used for this research is qualitative descriptive. This study provides an overview of the mastery of the Indonesian language through the teaching of the Indonesian language and national insight through the teaching of Pancasila and Civics Education (PPKn). The results of this research indicate that the Indonesian language proficiency and national insight of 5th-grade students in IB international schools still need improvement. However, the average results of the students' national insight increased from 60 to 76 after the learning process. Language proficiency and national insight are crucial in shaping the identity of students, especially for Indonesian learners. This is also important for foreign students as it relates to their current existence and helps them adapt. To address this issue, the school has implemented several policies to improve the Indonesian language proficiency and national insight of their students.